A facile synthesis of CDs from quinoa for nanosensors and bio-imagining. (2nd July 2020) - Xu, Dandan; Li, Yong; Li, Naixin; Lei, Fang; Liu, Jinliang; Shi, Ying; Yin, Luqiao; Zhang, Lei
Abstract: Carbon dots (CDs) with strong fluorescence were synthesized by a facial and green hydrothermal method using biomass quinoa as the carbon source. The as-prepared carbon dots (CDs) aqueous solution shows bright blue photoluminescence under the irradiation of UV lamp with a quantum yield of 14% and considerable luminescence stability and excellent strong photobleaching resistance. The as-prepared CDs was nontoxic for in vitro and in vivo applications. In addition, not only the as-prepared CDs were used for HeLa cells imaging, but also detect Fe 3+ ions in cells, and the ideal imaging pictures were obtained under excitation of 405 nm. The as-prepared carbon dots possessed excellent responsive properties towards Fe 3+ . The quenching phenomenon can be used to detect the Fe 3+ ions within a linear range of 0–300 μ mol l −1 with a limit of detection of 50 nmol l −1 .